Identifikasi Keanekaragaman Jenis Mangrove (Studi Kasus Desa Kuli, Kecamatan Lobalain, Kabupaten Rote Ndao, Provinsi Nusa Tenggara Timur) - Nelson Jose Leo; Maria M. E. Purnama; Pamona Silvia Sinaga (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Kuli Village , Lobalain District , Rote Ndao Regency has a relatively natural mangrove forest ecosystem. For the people of Kuli Village, the existence of mangrove forests which are very important as a support for their lives directly and indirectly has been felt by the people of Kuli Village. The most worrying thing about the destruction of mangrove forests is the loss of mangrove species which causes a decrease in the species diversity of mangrove forests. The purpose of this study was to identify the types of mangroves in the Coastal Area of Kuli Village, Lobalain District, Rote Ndao Regency, East Nusa Tenggara Province.This research was conducted in Kuli Village, Lobalain District, Rote Ndao Regency, East Nusa Tenggara Province .The determination of the measuring plot is done in a simple random sampling manner. The data collection techniques used in this study are primary data and secondary data. From the data collected, descriptive and quantitative data analysis was carried out. The results of the study obtained that there are 6 types of mangroves that grow, namely Perepat (Soneratia alba), Mangrove (Rizhopora apiculata), Pedada (Sonneratia caseolaris), White mangrove (Bruguiera cylindrica), Fire-fire (Avicennia marina) and Black Flames (Avicennia alba). The diversity index (H') of all types was obtained at 1.352. This shows that the level of diversity of mangrove species in Kuli Village is included in the moderate category .